CODE-SWITCHING IN THE EFL CLASSROOM: BARRIER OR BRIDGE? (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Code-switching, the practice of alternating between two or more languages or dialects within a conversation, is a common phenomenon in English as a Foreign Language (EFL) classrooms. This study investigates whether code-switching functions as a barrier to language acquisition or serves as a pedagogical bridge.